TOTAL ACID NUMBER REDUCTION OF NAPHTHENIC ACIDS USING SUBCRITICAL METHANOL WITH AND WITHOUT ACIDIC IONIC LIQUIDS - ZAFAR, FAISAL (2017)
The impurity, naphthenic acids (NAs), present in heavy crude oil create corrosion problem at different processing stages of oil and gas industry. The traditional total acid number (TAN) reduction processes are non-selective due to their respective drawbacks. The objective of this study was to reduce TAN ofNAs using subcritical methanol with and without acidic ionic liquids (AILs).